Pengaruh Kualitas Produk, Kemasan dan Persepsi Harga Terhadap Kepuasan Pelanggan - Rivana Aurelia Agustina; Meylani Tuti (Indonesian Journal Publisher, 2025)
The purpose of this study is to ascertain how customer happiness with Calf coffee in Indonesia is impacted by product quality, packaging, and price perception. With 209 respondents, the study was carried out quantitatively utilizing a survey method and purposive sampling technique. With the use of SmartPLS software, structural equation modeling, or SEM, was used to analyze the data The results showed that the three independent variables significantly and positively influenced customer satisfaction. Of the three, packaging had the greatest influence on satisfaction, followed by price perception and product quality. Sensory aspects such as acidity and intensity of taste, visual elements on packaging such as shape, material, and labels, and perceptions of price fairness were shown to contribute to shaping customer experience. Although product quality has the lowest influence compared to other variables, it remains an important factor in customer perception. This study provides important implications for coffee business actors in increasing competitiveness through packaging innovation and pricing strategies. The limitations of the study lie in the focus on a single brand and a certain time period. Further research is recommended to explore more other factors that influence customer satisfaction.